General Form is the most basic form of an equation and is used as a template to form equations designed to solve a specific problem.
The equation given is "<span>(x- -1)^2 +(y-1)^2 =225.0".
The general form of this Equation would be presented as
</span>·X (+/-) Y = Z
·X^2 (+/-) Y^2 = R1
<span>
-I hope this is the answer you are looking for, feel free to post your questions here on brainly in the future.</span>
Answer:
The correct answer is option B. 17
Step-by-step explanation:
It is given that, ZX bisects ∠WZY. If the measure of ∠YXZ is (6m – 12)°
<u>To find the value of m</u>
From the figure we can see that, triangle WYZ is an isosceles triangle.
ZW = ZY
Then <YXZ = <WXZ = 90°
It is given ∠YXZ = (6m – 12)°
(6m – 12)° = 90°
6m = 90 + 12 = 102
m = 102/6 = 17
Therefore the value of m = 17
The correct answer is option B. 17
Answer: C. y=25x+125
Step-by-step explanation:
it multiplies by 75 and adds 125 each time
Answer:
neither do I'm stuck on that one